2013
DOI: 10.1128/aac.00528-13
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Carriage of Epidemic Methicillin-Resistant Staphylococcus aureus 15 (EMRSA-15) Clone Observed in Three Chicago-Area Long-Term Care Facilities

Abstract: The spread of pandemic methicillin-resistant Staphylococcus aureus (MRSA) clones such as USA300 and EMRSA-15 is a global health concern. As a part of a surveillance study of three long-term care facilities in the Greater Chicago area, phenotypic and molecular characterization of nasal MRSA isolates was performed. We report a cluster of pandemic EMRSA-15, an MRSA clone rarely reported from the United States, detected during this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…In this study, differences in the antibacterial activities of ZnO-incorporated samples were apparent between Gram-positive and Gram-negative bacteria, presumably as a result of differences in the cell-wall structures: Gram-positive bacteria have a thick peptidoglycan layer (20–80 nm), whereas Gram-negative bacteria have a thinner layer of peptidoglycan (7–8 nm) and a second outer membrane. 52 In keeping with previous studies, 1822,42,51 Gram-negative bacteria were found to be less susceptible to dye- and NP-incorporated polymeric surfaces. This may be due to the reduced penetration of radicals through the double cell membrane of Gram-negative bacteria.…”
Section: Resultssupporting
confidence: 89%
“…In this study, differences in the antibacterial activities of ZnO-incorporated samples were apparent between Gram-positive and Gram-negative bacteria, presumably as a result of differences in the cell-wall structures: Gram-positive bacteria have a thick peptidoglycan layer (20–80 nm), whereas Gram-negative bacteria have a thinner layer of peptidoglycan (7–8 nm) and a second outer membrane. 52 In keeping with previous studies, 1822,42,51 Gram-negative bacteria were found to be less susceptible to dye- and NP-incorporated polymeric surfaces. This may be due to the reduced penetration of radicals through the double cell membrane of Gram-negative bacteria.…”
Section: Resultssupporting
confidence: 89%
“…8,10,19,22,43 Furthermore, EMRSA-15 has also been reported in other non-European countries, such as USA, 15 India, 14 and Malaysia; 20 however, in these locations it was not the predominant clone. EMRSA-15 has been recently reported to be found in high rates also in community settings in Portugal, suggesting the spillover of the clone from nosocomial settings into the community.…”
mentioning
confidence: 83%
“…A total of 991 positive cases from 172 different strains were confirmed, and the most prevalent strain was UK EMRSA-15 (289 cases). UK EMRSA-15 is present in 16 countries worldwide (Grundmann et al, 2010; Das et al, 2013). Here, we focus on this specific strain.…”
Section: Methodsmentioning
confidence: 99%
“…To address these issues, here we develop an agent-based network model-Bayesian inference system for estimating unobserved colonization and importation rates from simple incidence records. We use this system to infer the transmission dynamics of the most commonly diagnosed MRSA strain, UK EMRSA-15 (Grundmann et al, 2010; Das et al, 2013), from multiple Swedish hospitals (Materials and methods). Key features estimated include the number of infections acquired in hospital and imported from outside, as well as the locations of individuals with a high colonization probability.…”
Section: Introductionmentioning
confidence: 99%